John F. C. Turner y su visión relacional de la vivienda - Oyón, José Luis (2021)
The article reconstructs the relational conception of housing by John F. C. Turner, a thought about inhabiting where as important as the housing physical object are the relationships that its inhabitants maintain with the environment. This vision, taken in essence from Patrick Geddes, began to be forged in the late 1940s, was taking shape during his stay in Peru between 1957 and 1964 and reached his definitive theoretical expression when he moved to the United States. The article finally reflects on the important role played by the Peruvian and American anthropologists with which he collaborated in Lima, and the figure of Charles Abrams in that Turnerian conception